2000
DOI: 10.1097/00005110-200002000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Documentation

Abstract: After 2 years of experience with a basic computerized system for documenting care, the nursing leaders in an inner city hospital undertook a redesign process to create an effective and efficient system for documentation that also provided data for monitoring care processes, patient outcomes, and staff performance. The basic system was a source of frustration and dissatisfaction for nurses, physicians, and managers. The redesigned system has exceeded the expectations of staff and physicians and delighted manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This level of standardization is to promote decreased practice variability and improved patient outcomes. Standardization of nursing care enables nurse managers to monitor staff compliance with care standards and track improvements in care processes by validating interventions and determining the effectiveness of nursing care through research and clinical audit [18]. This enhances safety and reduces errors by incorporating the best available evidence for practice.…”
Section: The Study Settingmentioning
confidence: 99%
“…This level of standardization is to promote decreased practice variability and improved patient outcomes. Standardization of nursing care enables nurse managers to monitor staff compliance with care standards and track improvements in care processes by validating interventions and determining the effectiveness of nursing care through research and clinical audit [18]. This enhances safety and reduces errors by incorporating the best available evidence for practice.…”
Section: The Study Settingmentioning
confidence: 99%
“…18 On the other hand, provision of care requires the documentation of clinical information as an intrinsic aspect of routine clinical activity and is essential from both professional and legal standpoints. Thus, clinicians will consider a system to be efficient if the system reduces their documentation time, 19 even if the time savings do not translate into better patient care. 20 For this reason, in evaluating the impact of EHR on clinician activities, some studies use documentation time as a primary outcome and direct patient care time as a secondary outcome.…”
mentioning
confidence: 99%
“…Studies have investigated the effects of structured data documentation and found that it led to more comprehensive and multidisciplinary communication regarding patients’ needs and also more detailed information about interventions and actions plans. 24,98,89 According to the Donabedian Model, improvements in the structure of care (e.g. a Nutrition MDS) should lead to improvements in clinical processes that should in turn improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%